100-fold improvement in carrier drift mobilities in alkanephosphonate-passivated monocrystalline TiO2 nanowire arrays. (8th March 2017) - Mohammadpour, A; Wiltshire, B D; Zhang, Y; Farsinezhad, S; Askar, A M; Kisslinger, R; Ren, Y; Kar, P; Shankar, K
Abstract: Single crystal rutile titania nanowires grown by solvothermal synthesis are actively being researched for use as electron transporting scaffolds in perovskite solar cells, in low detection limit ultraviolet photodetectors, in photoelectrochemical water-splitting, and in chemiresistive and electrochemical sensing. The electron drift mobility ( μ n ) in solution-grown TiO2 nanowires is very low due to a high density of deep traps, and reduces performance in optoelectronic devices. In this study, the effects of molecular passivation of the nanowire surface by octadecylphosphonic acid (ODPA), on carrier transport in TiO2 nanowire ensembles, were investigated using transient space charge limited current measurements. Infrared spectroscopy indicated the formation of a highly ordered phosphonate monolayer with a high likelihood of bidentate binding of ODPA to the rutile surface. We report the hole drift mobility ( μ p ) for the first time in unpassivated solvothermal rutile nanowires to be 8.2 × 10 −5 cm 2 V −1 s −1 and the use of ODPA passivation resulted in μ p improving by nearly two orders of magnitude to 7.1 × 10 −3 cm 2 V −1 s −1 . Likewise, ODPA passivation produced between a 2 and 3 order of magnitude improvement in μ n from ∼10 −5 –10 −6 cm 2 V −1 s −1 to ∼10 −3 cm 2 V −1 s −1 . The bias dependence of the post-transit photocurrent decays in ODPA-passivated nanowires indicated that minority carriers were lost to trapping and/or monomolecular recombination for small values of bias (<5 V). Bimolecular recombination was indicated to be the dominant recombination mechanism at higher bias values.